(3YOI GdOGYj hfLGM GdSGYjs - (3GdCSOj, GdMdj, CHh GdYHGS, LeGd GdOjf, CMeO Hf eMeO Hf agO, J (B841(3g`s ((3eMeO UGOb Hf ejQRG eMeO Ndjds)
(3ChdgG (B:s
(3GdMeO ddg SGeY GdOYGA (B... (3aEf Gddg SHMGfg ef hahQ cQeg Yde GdOYGA hfOH Edjg hCdge GdSDGd hMK Ydjg hQZH aj eYGedI hGdEbOGe Ydjg hLYd aj efGLGJg SHH GdfLGI aj SDGdg ebGdjO GdYWGjG hGdgHGJ (B...s
(3BNQgG (B:s
.. (3hdG JYdegf GdefGabjf aEfgG OYhGJ eSJLGHI dbGFdgf Ef TGA Gddg hgh OYGA Cgd GdHjJ GdeYehQ Mhdg EPG cGfhG jWhahf Hg hdjcf gPG BNQ eG fedjg aj gPg GdQSGdI (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\227s
(3GdPQjYI (B15\1491s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs